Penerapan Model Pembelajaran Problem Based Learning (PBL) Berbantuan Media Puzzle - Erlin Erlina; Eka Lokaria; Lucy Arsi Purwasih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the completeness of science learning outcomes for fourth grade students at SDN 57 Lubuklinggau City after applying the Media Puzzle Assisted Problem Based Learning model to Science Learning Outcomes. The research method used is the pre-experiment design method with pre-test and post-test quasi-experiments. The population and sample in this study used one class, namely grade IV students with 22 students. The sampling technique used is Saturated Sampling technique. The instrument used by the researcher was in the form of essay questions which totaled 10 questions. Data collection techniques are taken using tests. Data were analyzed using the z-test formula. Based on the results of data analysis tests with a level of α = 5%, it shows that Zcount = 3.49 and Ztable = 1.64. because Zcount ≥ Ztable (3.49 ≥ 1.64). Which shows that Ho is rejected and Ha is accepted. Thus it can be concluded that the Problem Based Learning model assisted by Media Puzzle in the science learning outcomes of class IV SD Negeri 57 Lubuklinggau City is significantly complete with an average student learning outcome of 80.88. Keywords: Science, (PBL), Media Puzzle